The Influence of the Mind Map Based Discovery Learning Model on Student’s Historical Thinking Ability in Class XI History Subjects at SMA - Susi, Susi; Maryuni, Yuni; Putra, Arif Permana (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
The aim of this research is to determine the effect of the Mind Map-based Discovery Learning model on students' historical thinking abilities in history learning. The research method used is quantitative experimentation. Sampling uses non-sampling techniques. Data analysis shows that there is a significant influence on students' historical thinking abilities when using the Mind Map based Discovery Learning learning model and the Problem-based learning model. This is based on a historical ability hypothesis study with independent t-test calculations, it is known that the test value is 11.400 with sig. (2 tailed). 001 (sig. 2-tailed) < 0.05. It can be concluded that Mind Map media has an influence on the history abilities of students at SMAN 1 Pontang. Based on the research results, the Discovery Learning learning model can be recommended in history learning because it attracts curiosity and increases the ability to think historically. Students are able to understand basic concepts and good ideas to sharpen and improve cognitive skills and processes by enthusiastically following history learning.